Cyber Clash di Dunia Maya: Cyberwar dan Conflict Resolution Indonesia-Malaysia - Syafuan Rozi (Jurnal Kajian Wilayah, 2010)
Cyber clash between Malaysia and Indonesia netter in mailing-list and blogs has been raised. There are crack dramatic issues such as I hate Indon, I hate Malon, Indonsial and Malingsia in website. It has been look as serious cyber conflict indeed. Scholars looked it as a latent conflict. Some of netters and blogger have been advocated and established offensive clash such as, making provocation, telling bad reality and just few write peace messages toward two nations stereotypes. It has been expressed in virtual wars through acts of like and dislike expression toward bilateral relations such as cultural heritage claim, nusantara workers condition in Malaysia, territorial boundaries, smokes impact, illegal logging, terrorism actors, etc. This radicalism has increasingly become a bilateral concern since the Sipadan-Ligitan and Ambalat Block cases, illegal logging, haze and forest burning, and Indonesia workers cases emerged between 2007-2009 periods.